Fawlty Towers. The complete collection, remastered [videorecording (DVD)] - Spiers, Bob; Davies, John Howard, 1939-2011; Cleese, John; Booth, Connie; Scales, Prunella; Sachs, Andrew (BBC Video ; 2 Entertain ; Distributed by BBC Worldwide Americas ; Distributed by Warner Home Video, 2009)
Basil Fawlty is an inept and manic English hotel owner and manager who isn't cut out for his job. He's intolerant, rude and paranoid. Chaos frequently breaks loose as Basil tries to run the hotel. He is constantly under verbal (and sometime physical) attack from his unhelpful wife Sybil, and hindered by the incompetent, but easy target, Manuel, the Spanish waiter. Fortunately he has an intelligent and attractive maid to help him out of the various situations he gets into.